Efektivitas Model Reading Questioning and Answering (RQA) dalam Pembelajaran Online terhadap Kemampuan Kognitif Siswa pada Mata Pelajaran IPA Terpadu - Endang Fitrianingsih; Rusdi Hasan; Hilyati Milla (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effectiveness of the Reading Questioning and Answering (RQA) learning model in online learning on student learning outcomes. The method used is a quantitative quasi-experimental design with a non-equivalent control-group pre-test/post-test design. The research sample was taken by purposive sampling of the eighth grade students of SMPIT An-Nida' Lubuklinggau. The online learning media used is WhatsApp with data collection instruments in the form of cognitive learning outcomes tests with 20 multiple choice questions. The results showed that there was a significant effect of the RQA learning model in online learning on improving student learning outcomes in Integrated Science subjects at SMPIT An-Nida' Lubuklinggau. In conclusion, the RQA learning model is effective in improving student learning outcomes online in Integrated Science subjects at SMPIT An-Nida' Lubuklinggau. Keywords: Cognitive Learning Outcomes, Online Learning, RQA, WhatsApp